(untitled) (Portuguese Journal of Family Medicine and General Practice, 2007)
The assessment of the doctor-patient relationship throughout the last century, shifting between positive, negative and neutral views, is an inescapable consequence of the technical and scientific developments available to Medicine. Periods when the supremacy of technical knowledge has overshadowed the figure of the physician have been followed by times when the doctors fundamental importance is acknowledged. In this interactive and recurrent process, characteristic of the confrontation between dissimilar systems striving for one common purpose, the importance of the doctor-patient relationship has of late been highlighted as a crucial tool. It is one that follows principles and methods that lie beyond the ordinary presence of a doctor and a patient whose behaviour is confined to pre-scripted roles. The doctor-patient relationship is currently understood as a technology in constant evolution, helping the doctor to work in the best of circumstances, with maximum efficiency and a minimum of mishaps. By integrating both solid and forceful technological elements with the irreplaceable needs of human relations, the doctor-patient relationship has gained value in both complexity and demand. Building on a systematic outlook on society and the concept of complex adaptive systems, we shall seek to clarify how Balint groups, as tools of training and improvement of the doctor-patient relationship, have established a dialogue with new social contexts and with the health care system, maintaining and developing their ability to support the relational activity of General and Family Physicians.